Assessment of time window for sleep onset on the basis of continuous wrist temperature measurement. Issue 6 (3rd June 2022) - Partonen, Timo; Haukka, Jari; Kuula, Liisa; Pesonen, Anu-Katriina
ABSTRACT: The interactions of the principal circadian clock with the homeostatic sleep process create the time-sensitive window for easy falling asleep in the evening, which is affected by a thermoregulatory process. It has been hypothesized that the changes in skin and core body temperatures before the sleep onset might play a direct role in sleep regulation. To determine this time window, we recorded from 20 healthy participants (11 women and 9 men), aged 26–58 years, one overnight own-home ambulatory polysomnography and measured continuously wrist skin temperature with a wrist-worn accelerometer containing a skin temperature thermometer. Wrist skin temperatures which were read out from the thermometer of the accelerometers were modeled using linear mixed models, and the linear effect of time before the sleep onset on wrist temperature was analyzed using a mixed model with the sex and age as the covariates. We found that wrist skin temperatures increased on average by 0.6° (of Celcius) in 10 min prior to the sleep onset and could be tracked robustly along a slope of time (p = 0.004). Our current findings may be useful in further characterizing the window of time and its boundaries for easy falling asleep.